A rare case of facial palsy caused by Tuberculosis in 1 month old infant - Arif Aziz Nathani; Rabindran Chandran; Hemant Parakh (International Journal of Medical Research and Review, 2015)
Tuberculous presenting in early infancy is rare. Most expectant mothers with TB are asymptomatic & were discovered to have tuberculosis only after the diagnosis in their infant was made. We report an infant who presented with fever, Right sided cervical mass with ipsilateral LMN type facial palsy with ear discharge whose evaluation revealed Tuberculous. This report describes probably the youngest infant to be diagnosed with cervical mass of tuberculous origin presenting with facial paralysis.